Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 16 local authorities was 5.1 per cent. — the reason for this being large families tend to get preference for council houses, and are still overcrowded, although less so, in their new homes. Moreover, what would certainly be called overcrowding from the common sense viewpoint is not overcrowding by the official standard. For example, as a child under ten counts as half a person, and a baby under one year of age not at all, it allows parents and seven children under 10 to live in three rooms. VI.— CAPITALISM'S PALLIATIVES. The Relief of Poverty. Such social security as we have in this country has grown up piecemeal and unco-ordinated, and consists of a number of schemes separately administered. There are (1) Public Assistance — the net which catches those who fall clear of any other scheme ; (2) Unemployment Insurance ; (3) the Assistance Board ; (4) Old Age, Widows', and Orphans' Pensions ; (5) National Health Insurance ; (6) Workman's Compensation ; and (7) War Pensions. (2) Public Assistance. Public Assistance is administered according to varying standards by the County Councils and Borough Councils. It is the last relic of the Poor Law, dating back to 1601. It has been shorn of one function after another until now its scope is limited to the following : (a) temporary assistance to those awaiting it from some other source; (b) supplementation of inadequate income from another source (e.g., Old Age Pensions); (c) emergency relief to the wives and children of strikers); (d) relief to the sick poor. Its survival is anomalous. Alone of all the schemes for the relief of poverty, it is dependent on a means test. The Public Assistance authority must recover part or full cost of relief from the relatives of the recipient. Moreover, the stigma of the Poor Law still attaches to it, so that people are ashamed to apply for it, whereas they claim unemployment benefit or pensions without loss of self-respect. It is indeed time that Public Assistance was replaced by a comprehensive system of social security. (2) Unemployment Insurance. This was originally designed merely to tide a workman over a change of employment. But between the wars, unemployment grew to gigantic proportions. Between 1929 and 1939 the numbers of unemployed were as follows* :— * 1929-1936 are calculated on the quarterly figures quoted in Facts [f]or Socialists. 1937-42 are calculated from The Economist Monthly Statistics. 15X/2/98/13